Analisis Peningkatan Suhu Pada Kolom Saat Terbakar Menggunakan Lusas V16 - Rahmiasari Rahmiasari; Reni Suryanita; Enno Yuniarto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Fire is one of the factors causing failure in the reinforce concrete. The surface of the concrete will become black due to significant increase in the temperature. Cracks occur of an imbalance in volume changes exist between cement paste and aggregate. This study aims to analyze the effect of the rate of changes in temperature on the RC during the fire. The method used is to analyze the rate of changes in temperature according to ASTM E- 119 standard. Analysis was conducted by using finite element software, LUSAS v.16. The column specimen used in this study had rectangular ratio of 350 mm × 600 mm with the length of 4000 mm. The amount of longitudinal bars was 10D19, while the yield strength of bars and the concrete strength was 400 MPa and 45 MPa, respectively. The column element burned with a duration of 4 hours. The results showed there was a difference in term of temperature change’s rate between LUSAS v.16 and manual calculation was 3,7%. This research can be used as a reference on designing fireproof buildings so as to prevent building collapse during a fire.Keywords : ASTM E-119, rate of temperature, LUSAS v.16